2014
DOI: 10.1007/s00414-014-1091-0
|View full text |Cite
|
Sign up to set email alerts
|

Population data of 30 insertion–deletion markers in four Chinese populations

Abstract: In this study, we assessed 30 insertion-deletion polymorphisms (Indels) (Investigator DIPplex® kit) in four Chinese populations (n = 952) and evaluated their usefulness in forensic genetic applications. After the Bonferroni correction at a 95 % significance level (p = 0.0017), there were no deviations from the Hardy-Weinberg equilibrium observed except for the HLD114 locus in the Tibetan ethnic group studied. A high level of discrimination power was observed for the DIPplex® kit in four sample populations (CDP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…The inclusion of a candidate InDel locus to distinguish continental populations in the first part from dbSNP public database (https://www.ncbi.nlm.nih.gov/projects/SNP/) should conform to the following criteria: (1) The insertion or deletion fragments of all InDels should be in the range of 2–20 bp, and we have currently used 20 bp as upper limit for better catering to the increasing genotyping need for degradative samples in forensic practice; (2) All the InDel loci should be in the intron region to avoid the appearance of function‐related loci; (3) The frequency differences of the InDel loci for continental populations should be more than 0.4; (4) Only loci complying with the Hardy‐Weinberg equilibrium (HWE) would be further considered. Criteria for the second part of candidate InDels selection was set by consulting previous literatures reporting InDel population genetic data of the three Chinese populations (Han, Uyghur, Tibetan) . Given the consideration that the genetic structure similarities among most Chinese populations were much larger than continental populations, we attempted to set the threshold to select candidate AIM‐InDels for providing valuable information to distinguish one population from the other two populations to be 0.2.…”
Section: Methodsmentioning
confidence: 99%
“…The inclusion of a candidate InDel locus to distinguish continental populations in the first part from dbSNP public database (https://www.ncbi.nlm.nih.gov/projects/SNP/) should conform to the following criteria: (1) The insertion or deletion fragments of all InDels should be in the range of 2–20 bp, and we have currently used 20 bp as upper limit for better catering to the increasing genotyping need for degradative samples in forensic practice; (2) All the InDel loci should be in the intron region to avoid the appearance of function‐related loci; (3) The frequency differences of the InDel loci for continental populations should be more than 0.4; (4) Only loci complying with the Hardy‐Weinberg equilibrium (HWE) would be further considered. Criteria for the second part of candidate InDels selection was set by consulting previous literatures reporting InDel population genetic data of the three Chinese populations (Han, Uyghur, Tibetan) . Given the consideration that the genetic structure similarities among most Chinese populations were much larger than continental populations, we attempted to set the threshold to select candidate AIM‐InDels for providing valuable information to distinguish one population from the other two populations to be 0.2.…”
Section: Methodsmentioning
confidence: 99%
“…Mean values of PIC, Ho, and He of 35 InDels in five reference populations ranged from 0.3568 (JPT) to 0.3603 (CHB), 0.4681 (JPT and CDX) to 0.4854 (CHB), 0.4712 (JPT) to 0.4769 (CHB), respectively. By comparing with the results of 30 InDels in Beijing Han and Guangdong Han populations, we found these 35 InDels showed higher diversities in Chinese Han populations. Some researchers suggest that genetic markers with PIC more than 0.25 can provide reasonable genetic information.…”
Section: Resultsmentioning
confidence: 81%
“…Fst can evaluate genetic differentiations of different populations which is utilized to infer population structure and human migration [22]. A previous study [23] points out that small Fst values between populations meant low genetic [24] and Guangdong Han [25] populations, we found these 35 InDels showed higher diversities in Chinese Han populations. Some researchers [26] suggest that genetic markers with PIC more than 0.25 can provide reasonable genetic information.…”
Section: Genetic Distributions Of 35 Indels In Five Reference Populatmentioning
confidence: 69%
“…Guangdong Han [11], Shanghai Han [12], Yi [13], Xibe [14], South Korean [15], She [16], Beijing Han, Tibetan, Kazak, Uyghur [17], Dane [18], Hungarian [19], Basque, Central Spanish [20], Uruguayan [21], Uyghur1, Zhuang, Dong, Miao, Chengdu Han, Tibetan1 [22], Henan Han, Beijing Han1, Uyghur2, Tibetan2 [23], the population structure of Bai ethnic group was performed by the structure program. In the determination of K value (Supplementary Figure 1), the results of L( K ) showed that K =3, 4 depicted a plateau obviously.…”
Section: Resultsmentioning
confidence: 99%